Penerapan Layanan Bimbingan Kelompok untuk Meningkatkan Pemahaman Mahasiswa tentang Perilaku Konsumtif - Jasman Jasman; Anggi Fitria; Thaheransyah Thaheransyah; Sri Sugita (Institut Agama Islam Negeri (IAIN) Curup, 2022)
Consumptive behavior often has a negative impact on a person's life. Students, for example, often buy fashion products that exceed their abilities and needs. Efforts are needed to increase student understanding through group guidance services. This study aims to determine the implementation of group services in preventing student consumptive behavior. The research uses quantitative methods with the type of experimental research. The study used a pre-experimental research, with a one-group pretest-posttest design. The research instrument is a questionnaire, with purposive sampling with ten group members. Data processing with SPSS program analysis techniques. The results showed that the results of the pretest understanding of student consumptive behavior were mostly in the low category, after the guidance service treatment was held, the posttest results of understanding the consumptive behavior of students were mostly in the medium (30%) and high (40%). Based on the research results, the average student consumptive behavior has decreased or has changed, although not drastically with group guidance services. This can be seen at the 0.05 significance level, which is 2.645> 2.262, thus the hypothesis is accepted, meaning that group counseling guidance services can increase students' understanding of consumptive behavior at a significance level of 0.05.